A study of compliment responses among male and female Egyptian undergraduate students - Mostafa, Mariam (AUC Knowledge Fountain, 2009)
The present study aims to detect the variations in the compliment responses (CRs) between male and female Egyptian undergraduates, adding new dimensions to the study of CRs in the Egyptian context generally and among males and females specifically. The outcomes of the study will provide implications about the linguistic forms of compliment responses across males and females at the undergraduate level and also about the social decorum and value systems of Egyptian teenagers represented by university students. A similar study was piloted in the spring semester of 2013, with a small convenient sample (28 students from a private University in Cairo). The tools for collecting data, for the current study, were an eight-point discourse completion task (DCT) and field notes. The sample for the current study is composed of 120 DCT takers and 83 collected field notes, which make a total of 1042 compliment responses. The compliments were labeled and categorized into 25 micro categories and then grouped into four macro categories (accept-reject-evade and other). The analysis of the data showed that males and females preferred accepting compliments and that rejecting rarely happens. The findings based on the micro analysis also revealed how differently males and females utilize compliment responses in terms of politeness, meaning conveyed and language.